2005
DOI: 10.1128/iai.73.11.7765-7767.2005
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Epithelial Cell Anti- Candida albicans Activity Is Associated with Protection against Symptomatic Vaginal Candidiasis

Abstract: Vaginal epithelial cell (VEC) anti-Candida albicans activity, despite being measured in vitro, is considered an innate host defense mechanism. This was supported further by the fact that women protected from symptomatic infection following a live intravaginal Candida challenge had increased VEC anti-Candida activity compared to those who acquired a symptomatic infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 16 publications
0
35
0
5
Order By: Relevance
“…In fact, several forms of immunoregulation seem to be in place to inhibit such responses (11,19,26). Instead, innate immunity by epithelial cells appears to provide some level of protection through noninflammatory processes involving direct contact with Candida (3,29,39). To further investigate factors associated with susceptibility to infection, a human live challenge was established where healthy women were given an intravaginal inoculation of C. albicans and followed for the natural history of infection (10).…”
mentioning
confidence: 99%
“…In fact, several forms of immunoregulation seem to be in place to inhibit such responses (11,19,26). Instead, innate immunity by epithelial cells appears to provide some level of protection through noninflammatory processes involving direct contact with Candida (3,29,39). To further investigate factors associated with susceptibility to infection, a human live challenge was established where healthy women were given an intravaginal inoculation of C. albicans and followed for the natural history of infection (10).…”
mentioning
confidence: 99%
“…According to (Barousse et al, 2005) there is an important anti-Candida activity in epithelial cells, raising the hypothesis that the VVC susceptibility is associated to signs from vaginal epithelial cell interaction with Candida, which promotes clinical symptoms such as leukocyte inflammatory response, but no protective, while VVC resistance is associated to the lack of signs and/or antifungal epithelial cells activity and absence of inflammation (Fidel, 2007;Jaeger et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It is still not clear though what causes either this temporary or permanent disturbance! It's been suggested that VVC is associated with signals that promote a non-protective inflammatory leucocyte response leading to the clinical symptoms [1,28]. Alteration of the vaginal ecosystem in certain conditions, which have been identified as risk factors for VVC and RVVC, such as sexual intercourse, use of antibiotics and female hygienic products [29], may also contribute to development of genital candidiasis.…”
Section: Pathogenesismentioning
confidence: 99%
“…It is the second most common cause of vaginal infections after bacterial vaginosis (BV) [1]. Estimates indicate that 70%-75% of women of childbearing age worldwide experience at least one episode during their lifetime, and 5%-10% of women with a primary episode of VVC experience frustrating recurrent infections (RVVC) [2], defined as at least three-four specific episodes within one year [3,4].…”
Section: Introductionmentioning
confidence: 99%